PENGARUH MEDIA GAMBAR TERHADAP KEMAMPUAN MEMBACA PERMULAAN ANAK KELOMPOK A DI KECAMATAN WAIKASE TAHUN 2022 - Iye, Risman; Abdullah, Rudi (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2023)
This study aims to determine the effect of media images on the initial reading ability of group A children at Pembina State Kindergarten, Waikase sub-district in 2022. This study used a quantitative experimental Pre-experimental Design method with a one group pretest-posttest design. The sample in this study were group A children a total of 23 people consisting of 9 boys and 14 girls. Sampling in this study using nonprobability sampling with purposive sampling technique. Analysis techniques include normality test, hypothesis testing and statistical hypothesis. The results of the normality test obtained a significance value of 0.071 pretest and 0.122 posttest more than (>) 0.05 meaning that the data is normally distributed. The results showed that there was a significant effect of the use of media images on the initial reading ability of group A children. It can be seen from the significance value of initial reading ability of 0.000, less than 0.05 (0.000 <0.05) with a t-count value of 18.40 > t table 1.717 which means that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted there is a significant effect of the use of media images on children's early reading ability